The IVP New Testament commentary: Acts - Larkin, William J.; Briscoe, D. Stuart; Robinson, Haddon W.; Osborne, Grant R (Downers Grove. Illinois, InterVarsity Press, 1995)
In Acts, the sequel to his Gospel, Luke tells how the Holy Spirit transformed a ragtag band of believers into a unified, world-engaging church. In this commentary, readers will find an introduction with background material concerning authorship, date and purpose, as well as a summary of important theological themes. A passage-by-passage exposition follows that focuses on understanding what significance Acts had for its original readers in order to see its relevance for the church today. --from publisher description.
General preface -- Author's preface -- Introduction -- Outline of Acts -- Commentary -- Bibliography.
Includes bibliographical references (pages 394-422).
Keywords: Bible. -- Commentaries